2020
DOI: 10.1002/jbmr.4721
|View full text |Cite
|
Sign up to set email alerts
|

Sirt3 Promotes Chondrogenesis, Chondrocyte Mitochondrial Respiration and the Development of High-Fat Diet-Induced Osteoarthritis in Mice

Abstract: Understanding how obesity‐induced metabolic stress contributes to synovial joint tissue damage is difficult because of the complex role of metabolism in joint development, maintenance, and repair. Chondrocyte mitochondrial dysfunction is implicated in osteoarthritis (OA) pathology, which motivated us to study the mitochondrial deacetylase enzyme sirtuin 3 (Sirt3). We hypothesized that combining high‐fat‐diet (HFD)‐induced obesity and cartilage Sirt3 loss at a young age would impair chondrocyte mitochondrial fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…However, a most recent work by Zhu et al reported that cartilage-specific deletion of SIRT3 ameliorates cartilage degeneration and synovial hyperplasia in high-fat diet (HFD)-induced metabolic OA model. [43] The enhanced glycolysis and suppressed mitochondrial fatty acid metabolism induced by SIRT3 loss may serve as the leading causes. Differing from other cell types, owing to the avascular structure, in vivo, chondrocytes produce energy mainly though anaerobic respiration.…”
Section: Discussionmentioning
confidence: 99%
“…However, a most recent work by Zhu et al reported that cartilage-specific deletion of SIRT3 ameliorates cartilage degeneration and synovial hyperplasia in high-fat diet (HFD)-induced metabolic OA model. [43] The enhanced glycolysis and suppressed mitochondrial fatty acid metabolism induced by SIRT3 loss may serve as the leading causes. Differing from other cell types, owing to the avascular structure, in vivo, chondrocytes produce energy mainly though anaerobic respiration.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT3 regulates mitochondrial functions and maintains redox homeostasis to prevent oxidative stress via its deacetylation activity in chondrocyte (36). Seahorse-based assays supported a mitochondrial-to-glycolytic shift in chondrocyte metabolism after SIRT3 deletion, resulting in energy shortage, which indicated that SIRT3 is crucial for mitochondrial respiration (37). In addition, Chen et al reported that AMPK and SIRT3 can regulate each other, and their expression and activity are always consistent in chondrocytes, which suggests the existence of an AMPK-SIRT3 positive feedback loop (38).…”
Section: Sirts and Energy Metabolismmentioning
confidence: 96%
“…SIRT3 regulates mitochondrial functions and maintains redox homeostasis to prevent oxidative stress via its deacetylation activity in chondrocyte ( 36 ). Seahorse-based assays supported a mitochondrial-to-glycolytic shift in chondrocyte metabolism after SIRT3 deletion, resulting in energy shortage, which indicated that SIRT3 is crucial for mitochondrial respiration ( 37 ). In addition, Chen et al.…”
Section: Sirts and Energy Metabolismmentioning
confidence: 99%
“…Moreover, it enhances mitochondrial respiration and fatty acid metabolism, thereby promoting HFD-induced OA. However, the deletion of Sirt3 plays a detrimental role in chondrogenesis when using a murine bone marrow stem cell pellet model, so its role on cartilage homeostasis has yet to be fully elucidated [ 93 ].…”
Section: Histone Modifications In Oamentioning
confidence: 99%